ANALISIS RISIKO RANTAI PASOK MATERIAL TERHADAP KETERLAMBATAN PELAKSANAAN PROYEK KONSTRUKSI: (STUDI KASUS RSUD SAM RATURALANG TONDANO) - Bryan F Hermanus; Shirly S. Lumeno; Jeffrey A. Delarue (Sustainable Construction (SUSCON), 2024)
The construction project requires the supply of material of pebbles, sand, cement, and iron bones, and others as materials to build a building structure. If there’s a problem with material procurement, it can affect the entire project process. This research aims to untutk Knowing the material supply chain application system, Identifying dominant risk variables, and Preparing risk responses to dominant risks. The method used in this study is the Severity Index using the probability table of impact. The application and flow of the supply chain of materials started from the contractor who ordered the material to the supplier, the materials used in the construction work obtained from two suppliers namely : CV Core Jaya and CV Eastern Light. Of the 13 variables analysed, one variable falls into the high-risk category, namely variable C1. (Pemesanan tambahan karena perubahan spesifikasi). Risk response to variable C1 (Additional orders due to changes in specifications) means that the contractor must claim liability to the supplier if the specifications of the material sent by the vendor do not correspond to what the contracting party ordered to be replaced with the material in accordance with the specification requested by the contractant, and also the contractors need to prepare an extra budget as a reserve budget if from time to time there is a change in the material price when making additional orders.